Malignant glomus tumor of prostate: A case report - Sun, Zhanxin; Sun, Fuzhen; Yu, Chunhong; Xiao, Helong; Xu, Qingle; Gao, Bo; Guo, Liuxiong; Liu, Junjiang; Li, Shoubin (Frontiers in Oncology, 2023)
We reported an 85-year-old patient with malignant glomus tumor (GT) of the prostate, he presented with urinary frequency for more than 2 years, and gross hematuria for 7 days. Computed tomography scan showed the prostate was marked irregularly enlarged and the boundary between the prostate and the posterior wall of the bladder was unclear. Bilateral kidneys and ureters were dilated. Biochemical examinations showed that the serum potassium was 7.24 mmol/L and the serum creatinine was 974.6 umol/L. Transurethral diagnostical resection was performed after restoring homeostasis through several times of bedside blood filtration. The pathological diagnosis was malignant GT. The patient’s renal function recovered after bilateral nephrostomy, and he refused further treatment and out of contact after 9 months. We summarize the clinical and histopathologic features of malignant GT of the prostate in order to improve the early recognition of the disease by clinicians.